PHENOLIC COMPOSITION AND ANTIOXIDANT ACTIVITY OF RAW SEEDS, GREEN SEEDS AND SPROUTS OF TEN FABA BEAN (VICIA FABA) CULTIVARS CONSUMED IN EGYPT - RAGAB EL-MERGAWI; HANAN A.A. TAIE (International Journal of Pharma and Bio Sciences, 2014)
Faba beans are widely consumed in Egypt as a vegetable by many ways. A study was conducted to determine the levels of phenolic compounds and antioxidant properties of raw seeds, green seeds and sprouts of ten faba bean cultivars commonly consumed in Egypt. Nubaria 2, Sakha 2 and Nubaria 1 cultivars showed higher amounts of phenolic compounds and exhibited the highest antioxidant activities (DPPH and FRAP). Four flavonoid constituents, myricetin, daidzein, apigenin and quercetin, were detected in tested faba bean seeds using HPLC with variable concentrations. For all tested cultivars, the mean values of total phenolics, tannins, total flavonoids, DPPH and FRAP in green seeds reached 342%, 485%, 267%, 439% and 136% relative to those found in raw seeds, respectively. The study concludes that the green faba bean seeds afforded an important source and good adequate level of antioxidants for daily inclusion in the human diet.